Analysis of issues of generic medicine supply chain using fuzzy AHP: a Pilot study of Indian public drug distribution scheme. Issue 1 (31st December 2020) - Shweta; Kumar, Dinesh
Abstract : Purpose: Integrated supply chain in pharmaceutical industry requires organized planning and modeling of each strategic element of pharmaceutical supply chain (PSC). The aim is to coordinate each activity of PSC and design a robust strategy to make the system hassle-free. Each activity of industry is interdependent and follows certain co-relations with each other. The paper focuses on the four most significant identified issues in PSC and analyses the weightages of these issues and their sub issues with respect to cost incurred and time taken to manage whole chain of supply. Design/methodology/approach: Fuzzy analytical hierarchy process methodology has been applied to rank the issues which consume maximum time and/or costs. Findings: The derived result shows that warehouse design and management (WDM) consumes more than one third of the total time and around half of the total cost. Other than WDM, process of supplier selection for procurement is second most time and cost consuming issue. The derived results are discussed and provided to the field experts of the area. The analysis will be useful for decision makers to economize PSC. Research limitations/implications: The study is limited to PSC; hence, result may vary with other practical situations. Practical implications: This generated scope for further research on how to minimize the weightage of WDM for cost and time in PSC industry so that decision-makers can optimize the economic system of PSC. Originality/value: The research is based on the field survey of India's largest generic medicine distributing company in the government sector; hence, analysis has been performed on real situation.